8(x+6)-24=4(2x+5)

Simple and best practice solution for 8(x+6)-24=4(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+6)-24=4(2x+5) equation:


Simplifying
8(x + 6) + -24 = 4(2x + 5)

Reorder the terms:
8(6 + x) + -24 = 4(2x + 5)
(6 * 8 + x * 8) + -24 = 4(2x + 5)
(48 + 8x) + -24 = 4(2x + 5)

Reorder the terms:
48 + -24 + 8x = 4(2x + 5)

Combine like terms: 48 + -24 = 24
24 + 8x = 4(2x + 5)

Reorder the terms:
24 + 8x = 4(5 + 2x)
24 + 8x = (5 * 4 + 2x * 4)
24 + 8x = (20 + 8x)

Add '-8x' to each side of the equation.
24 + 8x + -8x = 20 + 8x + -8x

Combine like terms: 8x + -8x = 0
24 + 0 = 20 + 8x + -8x
24 = 20 + 8x + -8x

Combine like terms: 8x + -8x = 0
24 = 20 + 0
24 = 20

Solving
24 = 20

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x=172+3x | | x=172 | | -6t^2+24t+14=t | | 2x-5y=36 | | 2x-17=-17+x+2 | | -(6-(a+1))=9-(5-(2a-3)) | | 10=2(h+2) | | -9x-8=6x+1 | | b-8+2b=15 | | x-8x^3+2=0 | | 4x^2=13x^2-9 | | (19b-7)-9(2b+3)=-6 | | 5=4q-7 | | -8t^2+48t-30=0 | | 1=2b-1 | | 5x+206x+30=3 | | 19-7-9(2b+3)=-6 | | 6(1)-y=9 | | -100=0.25x | | 0=t^2+6t-9 | | 4c+5=4c+3 | | 10=lx-3l | | x^2-6x-11=-8 | | 18=3p+6 | | k-10=7 | | 0.35(16-x)+x=0.40(16) | | x+2x+(x+8)= | | -16t^2+20t+240=0 | | 7xa-11=31 | | 2x+y+3z=6 | | 3.7+t=9.45 | | 6x+15y=4 |

Equations solver categories